2022
DOI: 10.1002/adfm.202201449
|View full text |Cite
|
Sign up to set email alerts
|

Edge‐Assisted Epitaxy of 2D TaSe2‐MoSe2 Metal–Semiconductor Heterostructures and Application to Schottky Diodes

Abstract: Van der Waals (vdWs) heterostructures based on 2D metals and semiconductors have attracted considerable attention due to their excellent properties and great application potential in next-generation electronic and optoelectronic devices. To obtain such vdWs heterostructures, the conventional approach with artificial exfoliation and stacking of 2D metals onto 2D semiconductors in the vertical direction is still far from satisfactory, because of the low yield and impurity-involved transfer process. Here, two-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…[25] From the SAED pattern results, we concluded that our samples grew along both lateral and vertical architectures. This growth phenomenon has been observed in other heterostructures, such as TaSe 2 -MoSe 2 [27] and SnS-SnS x Se (1−x) . [39] Figure 4i shows a high-resolution ADF-STEM image of the NbS 2 layer with a perfect hexagonal arrangement.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…[25] From the SAED pattern results, we concluded that our samples grew along both lateral and vertical architectures. This growth phenomenon has been observed in other heterostructures, such as TaSe 2 -MoSe 2 [27] and SnS-SnS x Se (1−x) . [39] Figure 4i shows a high-resolution ADF-STEM image of the NbS 2 layer with a perfect hexagonal arrangement.…”
Section: Resultssupporting
confidence: 72%
“…CVD is an efficient method for producing high-quality interfaces with controllable thicknesses on a large scale. Two-step CVD growth serves as a universal method for growing diverse M-S TMDs heterostructures, such as NbS 2 -MoS 2 , [24] NbS 2 -WS 2 , [25,26] TaSe 2 -MoSe 2 , [27] NbTe 2 -WSe 2 , [28] and VSe 2 -WSe 2 . [29] However, the edges and surface of the as-grown first layer can be oxidized in air before the second growth step, inducing an undesirable heterointerface.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Chemical vapor deposition (CVD) is a widely recognized and efficient technique for the large‐scale production of high‐quality m–s heterostructures. Various m–s heterostructures, such as NbS 2 –MoS 2, [ 24,25 ] NbS 2 –WS 2 , [ 26 ] VSe 2 –WSe 2 , [ 27 ] TaSe 2 –MSe 2 , [ 28 ] and NbTe 2 –WSe 2 , [ 29 ] have been successfully grown by CVD. However, these investigations solely concentrated on heterostructures involving monolayer TMD semiconducting layers.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include manufacturing clean edge contact to 2D semiconductors, 30,31 phase engineering of 2D semiconductors to construct planar metal–semiconductor heterostructures, 32,33 formation of clean interfaces via van der Waals (vdWs) contacts using graphene, 34 mechanical transfer of metal films, 35 using hexagonal boron nitride (h-BN) as the tunnel barrier, 10 and synthesis of metal–semiconductor heterostructures by vapour phase epitaxy. 36–42 Among these strategies, vapour phase epitaxy technology is an effective method to create vdWs heterostructures with a low contact barrier at the clean vdWs interface. For instance, Zhang et al 38 demonstrated a controllable epitaxial growth of NbS 2 -WS 2 lateral heterostructures via a facile “two-step” chemical vapor deposition (CVD) route.…”
Section: Introductionmentioning
confidence: 99%